Poradnictwo karier w sektorze szkolnictwa zawodowego – refleksje – dylematy – pytania - Piorunek, Magdalena (Kultura-Społeczeństwo-Edukacja, 2016)
The text brings closer the career (vocational) guidance issues in the context of the vocational education specificity. Liquid modernity, with multidirectional changes occurring at a great speed, and growing requirements of the competitive labour market have become fertile soil for the growth of all sorts of guidance services, i.e. activities that concern the entire human life and treat individuals in a holistic way. Being one of them, the career guidance has travelled a long way undergoing a paradigmatic change of its objectives and tasks and of other aspects, i.e. how a relation with a client starts or what methods are applied. Vocational school students are one of those groups where career structuring is in demand. Being a weak link in Poland’s education system before the economic and political system transformations of 1989, after this date the group actually has started drifting, losing to the growing educational aspirations and the boom of secondary education that opened the door to increasingly popular higher education. Current efforts to restore vocational education need to be coupled with career guidance services that are provided professionally to the present and future vocational school students. Assumptions of these career guidance activities do not seem to differ basically from the general assumptions applied in the holistic guidance, which does not mean that a search for methods suited to this group of young people should be discontinued.